2008
DOI: 10.1007/s11605-008-0629-1
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Barrett Esophagus with Early Neoplasia by Radiofrequency Ablation, with or without Endoscopic Resection

Abstract: Background Radiofrequency ablation is safe and effective for complete eradication of nondysplastic Barrett esophagus (BE). The aim was to report the combined results of two published and two ongoing studies on radiofrequency ablation of BE with early neoplasia, as presented at SSAT presidential plenary session DDW 2008. Methods Enrolled patients had BE ≤12 cm with early neoplasia. Visible lesions were endoscopically resected. A balloonbased catheter was used for circumferential ablation and an endoscope-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 34 publications
4
85
2
2
Order By: Relevance
“…EMR has been shown to be successful following cryospray ablation therapy but not as feasible following radiofrequency ablation [9,23]. Our study demonstrated similar technical success of EMR in three cases following cryospray ablation.…”
Section: Discussionsupporting
confidence: 54%
“…EMR has been shown to be successful following cryospray ablation therapy but not as feasible following radiofrequency ablation [9,23]. Our study demonstrated similar technical success of EMR in three cases following cryospray ablation.…”
Section: Discussionsupporting
confidence: 54%
“…In one trial of photodynamic therapy plus proton-pump inhibitors compared with proton-pump inhibitors alone, progression to cancer was significantly decreased in the photodynamic-therapy group (13% vs 28%). In the other, which assessed endoscopic radiofrequency ablation in patients with Barrett' s esophagus and high-grade dysplasia, radio frequency ablation was more effective in eradication of high-grade dysplasia than a proton-pump inhibitor alone, and the progression to cancer was lower (4% vs 22%) during short-term follow-up [74][75][76][77] .…”
Section: Preventive Factorsmentioning
confidence: 99%
“…Buried Barrett's glands have been evaluated in all RFA studies showing positive result in one of 5000 biopsies. Re-EMR specimens after ablation did not show any buried glands [237]. Neo-squamous epithelium on EMR specimens in a group of 22 post-RFA patients with baseline BE with IMC or HGD showed no evidence of persistent genetic abnormalities or buried BE glands [243].…”
Section: Endoscopic Ablative Therapiesmentioning
confidence: 81%
“…Stricture formation rate was up to 6%, much lower than the rate associated with EMR [234]. In combination with EMR complications are found more frequently [237,238]. Nontransmural laceration associated with circumferential RFA following EMR was observed in 7% of patients, which occurred only at the level of the EMR.…”
Section: Endoscopic Ablative Therapiesmentioning
confidence: 86%
See 1 more Smart Citation